Investigation and Management of Renal Stones - Barrett, Brendan J. (1989)
Renal stones are a major source of morbidity and health care expenditure. Stone-forming patients may be grouped according to the etiological factors of their disease. Investigation begins with an appropriate history and physical examination, followed by selected laboratory tests aimed at discovering factors that may be contributing to stone formation and also at classifying the activity of the stone disease. Management depends on timely surgical procedures to deal with problematic stones and on advice concerning fluid intake, dietary modification, and in some cases, drug therapy to prevent further stone formation.